IDENTIFIKASI GAYA BELAJAR MAHASISWA - Papilaya, Jeanete Ophilia; Huliselan, Neleke (Faculty of Psychology, Diponegoro University, 2016)
The objective of this study was to identify learning styles of students. The approach used in this study is a quantitative approach with survey method. The variable in this study is a single variable , namely the identification of student learning styles. The study population is students of Guidance and Counseling FKIP Pattimura University totaling 388 people. Samples were used as samples in the amount of 10% of the population of 39 people. The sampling technique using Simple Random Sampling. Learning styles questionnaire prepared based on the opinion of De Poter & Hernacki is used as a data collection tool. Learning styles identified as visual learning style, auditorial learning style, and kinesthetic learning style. Data analysis techniques in this study is the descriptive statistical analysis methods. Based on the survey results revealed that students of guidance and counseling FKIP Pattimura University has a tendency to one learning style. Of the 39 students found that 6 students had a tendency visual learning style, 20 students have a tendency to auditory learning style, 1 student has a tendency kinestheticlearning style, and 12 students have a tendency to mix between learning styles and learning styles visual auditorylearning styles.